Extrauterine gestational choriocarcinoma: Report of two cases - Chan, Donald P.C.; Wong, W.P. (Lippincott, Williams & Wilkins, 1970)
In two cases of extrauterine gestational choriocarcinoma, one patient had a pelvic mass at the base of the right broad ligament and the other had multiple lesions in both lungs 3 years after a total hysterectomy for a molar pregnancy. The mode of origin of such malignant trophoblastic disease of the pelvis and of the lungs is problematical. Trophoblastic emboli constitute the most likely source. These cells must remain dormant for many months or years before they assume a malignant role. Although chemotherapy should be the mainstay in the curative treatment of choriocarcinoma, extirpative surgery also has a definite and important role. © 1970 The American College of Obstetricians and Gynecologists.